Specialization and performance: Evidence from NCAA 4 400 m relay times - Candon Johnson; Robert Schultz; Joshua C. Hall (Economies, 2020)
This paper investigates the impact of having open 400 meter (400 m) runners on NCAA relay teams. Using data from 2012-2016 containing the top 100 4 x 400 m in each NCAA Division relay times for each year, it is found that more 400 m specialists lead to an increase in the overall performance of the team, measured by a decrease in relay times. The effect is examined across Division I-III NCAA track teams. The results are consistent across each division. We view this as a test of the role of specialization on performance. Using runners who specialize in 400 m races should increase overall team performance as long as specialization does not lead to an inefficient allocation of team human capital. An additional performance measure is used examining the difference between projected and actual relay times. Divisions I and II are found to perform better than projected with an increase in 400 m runners, but there is no effect found in Division III.
Keywords: J31; L20; 330; Division III; peer effects; running; specialization